Insights of energy and its trade networking impacts on sustainable economic development. (15th February 2023) - Ashfaq, Saleha; Tang, Yong; Maqbool, Rashid
Abstract: Oil and gold are considered as the most vigor influencer for any economy. In this research volatility spillover networking among the oil (energy), gold, and Asian leading emerging stock markets are constructed by the coalescence of two approaches BEKK-GARCH and complex networking. The data consists of the daily return of sixteen Asian countries' stock markets, an index of the Asia Pacific, and future prices of oil and gold contracts for the period of 01–01-2010 to 31-05-2020. It covers all the recent shocks of the current decade to study the impact of these crises. The data is further divided into four sub-periods as well for this research. The results of our total period detect that commodities of oil and gold receive more volatility spillover than transfer it to stock indices of Asia Pacific countries. Moreover, it is also observed that, as compared to oil, gold had more strong significant spillover linkages. Among all Asian economies, the Chinese stock markets had more influence on the price movement of oil and gold. Whereas, India had more significant correlations with other neighboring stock indices. The results of this research not only provide the facts about the interconnection of oil, gold, and Asian Pacific countries in the current scenarios but also give very useful directions for future researchers, investors, and hedgers, as well as for policymakers interested in the Asian region. Highlights: highlights spillover networking among oil, gold, and Asian stock markets. applies the coalescence of two approaches BEKK-GARCH and complex networking. employs the daily returns of sixteen stock markets and future prices. shows the oil and gold receive more volatility spillover than transfer to stock. illustrates that compared to oil, gold had more strong spillover linkages.